2013
DOI: 10.1186/1750-1172-8-38
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Friedreich’s Ataxia on health-care resource utilization in the United Kingdom and Germany

Abstract: BackgroundFriedreich’s Ataxia (FRDA) is a neurodegenerative disorder that causes progressive damage to the central and peripheral nervous systems having a significant impact upon quality of life. With little information in the literature, cross-sectional observational studies were conducted in the UK and Germany to collect data on resource use and the burden of the disease on individuals and their caregivers.MethodsCross-sectional observational studies were conducted in the UK and Germany to estimate the burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…The top 3 drivers of health care cost were similar for ALS. A prospective study that evaluated the annual cost related to Friedreich’s Ataxia, a neuromuscular disorder due to a genetic mutation in the mitochondrial protein frataxin, showed that hospitalizations contributed to 21% of total direct medical costs in the UK [ 20 ], which is consistent with our finding. In MS, prescription drug was the single biggest driver of health care cost, as evident by the number and cost of disease modifying treatments approved for MS.…”
Section: Discussionsupporting
confidence: 90%
“…The top 3 drivers of health care cost were similar for ALS. A prospective study that evaluated the annual cost related to Friedreich’s Ataxia, a neuromuscular disorder due to a genetic mutation in the mitochondrial protein frataxin, showed that hospitalizations contributed to 21% of total direct medical costs in the UK [ 20 ], which is consistent with our finding. In MS, prescription drug was the single biggest driver of health care cost, as evident by the number and cost of disease modifying treatments approved for MS.…”
Section: Discussionsupporting
confidence: 90%
“…The private and public funding ratios were compared for persons with FRDA and the general population to identify any discrepancies. This study came second to a study on healthcare resource utilization of FRDA patients in the United Kingdom and Germany (Giunti et al, 2013). …”
Section: Objectivesmentioning
confidence: 89%
“…This is in part because large samples are required to generate sufficient numbers of affected patients. One longitudinal prospective study from Europe 15 demonstrated significant annual costs related to Friedreich’s Ataxia (FA), a neuromuscular disorder that impacts mitochondrial function. They found that hospitalizations contributed to approximately 20% of total direct medical costs in the UK.…”
Section: Discussionmentioning
confidence: 99%